Cordycepin exhibits a suppressive effect on T cells through inhibiting TCR signaling cascade in CFA-induced inflammation mice model. (3rd March 2020) - Wang, Xiaoli; Xi, Deshuang; Mo, Jian; Wang, Ke; Luo, Yu; Xia, Erbin; Huang, Rong; Luo, Shunrong; Wei, Jiao; Ren, Zhenghua; Pang, Hui; Yang, Rirong
Abstract: Objective: Cordycepin has been shown to exhibit multiple pharmacological activities, such as antitumor, antifungi, antivirus, and immune-regulation activities, and is involved in the regulation of T cells. However, cordycepin that affects T cell activity is still not clear, and the molecular mechanism of cordycepin in regulation of TCR signaling has not yet been elucidated. In this study, the potential effect of cordycepin on T cells was observed in CFA-induced inflammation mice model, and the function of cordycepin in regulating TCR signaling cascade was investigated. Methods: A CFA-induced inflammation mice model was established for observing the effect of cordycepin on the thymus and spleen swellings, and T cell infiltration in paw tissue was detected by immunohistochemistry. The protein expression or phosphorilation was detected by western blotting, and the NFAT1 nuclear translocation was determined by fluorescence imaging. The cell proliferation, apoptosis, and IL-2 production were analyzed by CCK-8 method, flow cytometry, and ELISA. Results: In the mice model, the thymus and spleen swellings were suppressed and the T cell infiltration in paw tissue was inhibited by cordycepin at a concentration of 10 mg/kg. Although the expressions of ZAP70 and PLCγ1 were not significantly changed in the human T cell line Jurkat with cordycepin pretreatment, the CD3-antibody-induced phosphorylations of ZAP70 and PLCγ1 were markedly blocked. The protein level of p85 decreased when Jurkat cells were pretreated with cordycepin, and cordycepin blocked TCR downstream molecule Erk phosphorylation and NFAT1 nuclear translocation. Further investigation revealed that cordycepin inhibited T cell proliferation, reduced IL-2 production, and induced T cell apoptosis. Conclusions: These findings suggest that cordycepin regulates TCR signaling to inhibit excessive T cell activation in inflammation. Thus, cordycepin may be a potential therapeutic application in inflammation-associated diseases.